Innovative Virtual Reality Learning Media With a Problem-Based Learning Model to Enhance Cognitive Engagement - Eka Fitrajaya Rahman; Erna Piantari; Sophia Zuyyinasyam (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Engaging learning experiences are often more memorable and effective, contributing to long-term retention of knowledge. One effective approach to enhancing the appeal of educational content is through the development of innovative learning media that leverages digital technology. This study focuses on the creation of Virtual Reality (VR)-based learning media, which integrates video, audio, text, and music to enrich the educational experience. The aim is to optimize the learning process by utilizing VR to deliver compelling and immersive content. To further enhance learning efficiency with VR media, this research employs the Problem-Based Learning (PBL) methodology as the pedagogical framework. The development process of the learning media follows a design thinking approach to ensure the media is both engaging and educationally effective. Validation results from student assessments indicate that the VR learning media, incorporating the PBL method, has successfully improved students' cognitive abilities. The media demonstrated a gain value of 0.57, reflecting a moderate increase in learning outcomes.